Nosema Raphidiae Sp.N. (Microsporida, Nosematidae): A Microsporidian Pathogen Of The Predatory Snake-Fly Raphidia Ophiopsis (Raphidioptera: Raphidiidae) - Yaman, Mustafa; Radek, Renate; Tosun, Onur; Unal, Sabri (Aperta, 2009)
The microsporidium Nosema raphidiae sp.n., a new pathogen of the predatory snake-fly Raphidia ophiopsis is described based on light microscopic and ultrastructural characteristics. It infects the gut of R. ophiopsis. All development stages are in direct contact with the host cell cytoplasm. Meronts with one diplokaryon are spherical or ovoid and are 3.8 to 6.2 mu m. Sporonts are spherical to elongate and measure 4.2 to 6.2 mu m. Diplokaryotic sporonts divide once to produce two sporoblasts which mature into spores. Sporoblasts are elongated and measure 3.2 to 5.2 mu m in length. Fresh spores with nuclei arranged in a diplokaryon are oval and measure 4.13 +/- 0.25 mu m in length and 2.26 +/- 0.19 mu m in width. Spores stained with Giemsa's stain measure 3.80 +/- 0.25 mu m in length and 2.18 +/- 0.17 mu m in width. Spores have an isofilar polar filament with six or seven coils. All morphological and ultrastructural features indicate that the described microsporidium belongs to the genus Nosema. This species has been named Nosema raphidiae sp. n. after its host's genus.